Recent pharmacological developments in the treatment of perennial and persistent allergic rhinitis. (23rd March 2016) - Klimek, Ludger; Mullol, Joaquim; Hellings, Peter; Gevaert, Philippe; Mösges, Ralph; Fokkens, Wytske
ABSTRACT: Introduction : Allergic rhinitis (AR) has a major negative impact on patients' quality of life (QoL) and carries a high socio economic burden. This is particularly the case for patients who experience symptoms for extended periods of time (i.e. those with perennial (PAR) or persistent AR (PER), depending on the classification system used). This review covers available pharmacological advances and recent developments in the treatment of PAR or PER. Areas covered : Pharmacological AR treatment is used to reduce symptom burden and help restore patients' normal daily routine. Traditionally, non-sedating antihistamines and intranasal corticosteroids (INS) were the two drug classes recommended for use first line. These, along with antileukotrienes, decongestants, mast cell stabilizers and anticholinergics, constituted the bulk of the AR treatment arsenal. MP-AzeFlu (Dymista®, Meda, Solna, Sweden) is the most recent addition to that arsenal. It is a novel intranasal formulation of azelastine hydrochloride (AZE) and fluticasone propionate (FP) delivered in a single spray and has surpassed available therapies in terms of symptom control and treatment response. Other relatively new treatments for PAR or PER include H3 antihistamines, toll-like receptor (TLR) agonists, cellulose powders and micro-emulsions, novel biomolecular formulations and omalizumab. Each of these new additions is reviewed here. Expert opinion : A new AR drug class has recently been introduced (i.e. RO1AD58). Currently MP-AzeFlu is the only treatment option within this drug class. It can be estimated that combination treatments like MP-AzeFlu will become the mainstay of PAR and PER therapy since use will result in better compliance, improved efficacy over INS and a faster response together with good levels of tolerability. The challenge is to find other equally, or more effective, combination treatments, as has been the therapeutic standard in bronchial asthma for decades. The potential of biologics, as well as TLR-agonists and other new treatment options needs to be further evaluated.